2016
DOI: 10.1039/c6fo01295g
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive and functional properties of sour cherry juice (Prunus cerasus)

Abstract: Sour cherry juice (Prunus cerasus) is consumed as a nutritional supplement claiming health effects. The aim of the study was to evaluate the different properties of sour cherry juice in terms of antioxidant activity and inhibition of target enzymes in the central nervous system and diabetes. The content of polyphenols and anthocyanins was quantified. Different experiments were carried out to determine the radical scavenging properties of the juice. The activity of sour cherry juice was also tested in physiolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(25 citation statements)
references
References 33 publications
0
24
0
1
Order By: Relevance
“…53,54 A recent in vitro model has shown that anthocyanin-rich supplements significantly reduced certain types of ROS, 2,2-diphenyl-1-picrylhydrazy and superoxide radicals. 55 Anthocyaninrich blueberry extract induces a cellular upregulation of glutathione. Increases in glutathione mediate homeostatic levels of extracellular signal-regulated protein kinases that promote favorable learning and memory pathways.…”
Section: Figmentioning
confidence: 99%
“…53,54 A recent in vitro model has shown that anthocyanin-rich supplements significantly reduced certain types of ROS, 2,2-diphenyl-1-picrylhydrazy and superoxide radicals. 55 Anthocyaninrich blueberry extract induces a cellular upregulation of glutathione. Increases in glutathione mediate homeostatic levels of extracellular signal-regulated protein kinases that promote favorable learning and memory pathways.…”
Section: Figmentioning
confidence: 99%
“…The neutralization of DPPH radicals as antioxidant method was reported the first time by Blois et al [33]. In this case, the assay was carried out according to the modifications described by Casedas et al [34]. In 96-well microplates, each well contained 150 µL of extract and 150 µL of DPPH (0.04 mg/mL methanol solution).…”
Section: Dpph Radical Scavenging Activitymentioning
confidence: 99%
“…Xanthine oxidase and xanthine as substrate are responsible for the production of superoxide radicals [36]. The effects of fern extracts on superoxide radicals generated by X/XO were evaluated by measuring the formation of the NBT (nitrotetrazolium blue chloride)-radical superoxide complex [37] using a described procedure [34]. The reaction mixture was prepared every day as a consequence of reduced stability.…”
Section: Superoxide Radicals Generated By Xanthine/xanthine Oxidase (mentioning
confidence: 99%
“…Aqueous extracts prepared from several cultivars of sweet cherries inhibited the enzyme α glucosidase, which is involved in the intestinal absorption of carbohydrates [ 78 ]. Similarly, tart cherry juice and one of its main polyphenols known as chlorogenic acid inhibited enzymes α glucosidase and dipeptidyl peptidase-4 which are involved in promoting diabetes [ 79 , 80 ]. Tart cherry extract and select anthocyanins purified from it also inhibited the activity of human α amylase in vitro [ 81 ].…”
Section: Clinical Studies Involving Consumption Of Cherries and Thmentioning
confidence: 99%